Relationships Between Service Quality, Customer Loyalty and Customer Repurchase Intention: The Example of Health and Fitness Clubs - Ali Çağrı Gücal; Bülent Gürbüz (Pamukkale University, 2024)
This study was conducted with the aim of testing the relationships between service quality perceptions, customer loyalty levels, and customer repurchase intentions of customers in health and fitness clubs. The sample group for the study comprised 476 individuals (233 female, 243 male) exercising in health and fitness clubs. Participants answered the Turkish version of the "Service Quality Assessment Scale (T-SQAS)", the Turkish version of the "Loyalty Scale in Sport Services (T-LSSS)" and the Turkish version of the "Repurchase Intention Scale (T-RIS)." For the analysis, t-test, MANOVA, ANOVA, and Pearson correlation statistical methods were used. The most substantial gap between participant expectations and perception scores concerning service quality was observed in the "program" subscale, while conversely, the "locker room" subscale had the smallest difference. The means subscale scores for the "(T-LSSS)" of female participants were identified as being higher than those of male participants. There was a positive relationship between service quality, customer loyalty, and repurchase intention. Finally, it was evident that members were dissatisfied with the services offered, indicating an inconsistency between their expectations and the actual service delivery. Managers of health and fitness clubs should make the necessary effort to increase the service quality of their clubs to the highest level. Positive effects of service quality on the formation of repurchase intention, the first stage of creating loyal customers, will increase the competitive power of health and fitness clubs in the market.